Gastric cancer with lesion extending to spleen and perforation into free peritoneum - Gonçalves,Roberto (2017)
Summary Perforated gastric carcinoma is a rare condition that is hard to diagnose preoperatively. It is associated with advanced cancer stages and has a high mortality, particularly in cases presenting preoperative shock. Few studies have investigated the presentation and adequate management of these carcinomas. In addition, there are no reports in the literature on perforations extending to the spleen, as described in this case, making the management of these lesions challenging. Our article reports a case of gastric tumor perforation extending to the spleen, which presented as a perforated acute abdomen. The patient was treated with total gastrectomy and D2 lymph node resection with splenectomy and progressed well with current survival of one year at disease stage IV.